2005
DOI: 10.1002/ajim.20201
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer among enlisted Army women occupationally exposed to volatile organic compounds

Abstract: This study provides preliminary evidence that exposure to one or more of the study VOCs is associated with an increased risk of breast cancer. Further substance-specific, quantitative analyses are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 50 publications
1
38
2
Order By: Relevance
“…Many of the specific solvents were correlated with each other, reducing ability to attribute risk to particular compounds. In a retrospective cohort study, Rennix et al 106 found higher risk among U.S. Army enlisted women in jobs with likely medium or high solvent exposure (IRR ¼ 1.48; 95% CI, 1.01-2.07). Chang et al [107][108][109] reported higher incidence in a large cohort of electronics factory workers in Taiwan.…”
Section: Occupational Studiesmentioning
confidence: 99%
“…Many of the specific solvents were correlated with each other, reducing ability to attribute risk to particular compounds. In a retrospective cohort study, Rennix et al 106 found higher risk among U.S. Army enlisted women in jobs with likely medium or high solvent exposure (IRR ¼ 1.48; 95% CI, 1.01-2.07). Chang et al [107][108][109] reported higher incidence in a large cohort of electronics factory workers in Taiwan.…”
Section: Occupational Studiesmentioning
confidence: 99%
“…However, most VOCs are toxic, mutagenic, and carcinogenic to humans and are therefore detrimental to human health. In fact, long-term exposure to indoor and industrial sources can cause sick building syndromes [1] and occupational diseases [2,3]. Therefore, increasing attention has been paid to the carcinogenic and adverse effects of various VOCs on human health [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…1706 physical fitness and undergo frequent routine medical examinations. 23,24 Second, environmental exposures 25 and lifestyle choices, including those pertaining to reproduction and OC use, likely differ between these two groups.…”
Section: Introductionmentioning
confidence: 99%